2011
DOI: 10.1002/pola.24770
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene polymerization using novel titanium catalytic precursors bearing N,N‐dialkylcarbamato ligands

Abstract: Polymerization catalysts based on N,N-dialkylcarbamato complexes of titanium(IV) appear particularly interesting, because these novel catalytic precursors are rather cheap and easy to synthesize and handle. This contribution reports ethylene polymerization behavior of titanium(IV) complexes of general formula Ti(O2CNR2)4 R ¼ Me (I) and Et (II) and TiCl2(O2CNMe2)2 (III). These precursors in conjunction with methylaluminoxane resulted active catalysts for the polymerization of ethylene, affording high-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 87 publications
1
15
0
Order By: Relevance
“…and Table ). The molecular structure of IV closely resembles those previously reported for the analogous compounds Ti(O 2 CNR 2 ) 4 (R = Me, Et, and i Pr ). Thus, the Ti(IV) centre displays a pseudo ‐dodecahedral geometry being coordinated to eight O‐atoms.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…and Table ). The molecular structure of IV closely resembles those previously reported for the analogous compounds Ti(O 2 CNR 2 ) 4 (R = Me, Et, and i Pr ). Thus, the Ti(IV) centre displays a pseudo ‐dodecahedral geometry being coordinated to eight O‐atoms.…”
Section: Resultssupporting
confidence: 80%
“…The colourless solid was recovered by filtration and dried under vacuum at room temperature . Complexes I–III were prepared according to the literature …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The colorless solid was recovered by filtration and dried under vacuum at room temperature . Complexes I , II and III were prepared according to the previously published methods.…”
Section: Methodsmentioning
confidence: 99%
“…As a part of our investigation of the coordination behavior of titanium N,N ‐dialkylcarbamato complexes, we have found that these compounds, upon activation with methylalumoxane (MAO), catalyze ethylene homopolymerization reactions . As an expansion of this preliminary work, we synthesized two Ti(O 2 CNR 2 ) 4 complexes with R = Et ( I ) and R = Me ( II ) and the mixed chlorocarbamato derivative Ti(O 2 CNMe 2 ) 2 Cl 2 ( III ) and explored their catalytic potential in copolymerization reactions of ethylene with 1‐hexene (Scheme ).…”
Section: Introductionmentioning
confidence: 99%